Mechanical Modeling and Application of Frost Heaving Damage to Assembled Concrete Rectangular Canals in Seasonally Frozen Soil Region - Weidong Chang; Zhengyi Wang; Gang Li; Hua Tang; Aiqin Wang; Yuwei Ma (Advances in Civil Engineering)
In the design and upkeep of canals in areas of seasonal permafrost, resistance to frost heave is a critical factor for ensuring the stability of water conveyance canals. Mechanical modeling is the key to frost heaving-resistant design. In this study, the theory of elastic thin plates was used to build a mechanical model of frost heaving damage to rectangular canals. The model’s plausibility was confirmed using a prototype canal as an example, and the canal’s deformation, internal force, and stress distribution were examined. The findings demonstrate that, compared to beam theory, the internal forces and deformations computed by the model are not evenly distributed along the plate width; the base slab and side walls both saw their greatest deformations in the middle portion and two-fifths from the canal’s top, respectively; at the junction of the two, the bending moments and tensile stresses are maximum and distributions are consistent; transverse moments should be used as control moments in the structural design of canals, and stick feet should be placed at junctions to stop damage. In addition, the maximum normal frost heaving force and optimal thickness that four various canals can withstand were estimated, and the results were biased in favor of safety. The calculation’s results can serve as a theoretical guide for antifreeze design concrete rectangular canals in places that experience seasonal freezing.